Performance Test of Membrane Electrode Assembly in DAFC using Mixed Methanol and Ethanol Fuel with Various Volume Comparison - Dwi Hawa Yulianti; Dedi Rohendi; Nirwan Syarif; Addy Rachmat (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Direct Alcohol Fuel Cell (DAFC) performance is influenced by electrocatalysis reactions that occur in Membrane Electrode Assembly (MEA). In this study, MEA was made with Pt-Ru/C (anode) and Pt/C (cathode) catalysts. The results of the electrode characterization with XRD showed a carbon peak at 26.63° and Ru at 40.58°. Based on the results of Cyclic Voltammetry (CV) measurements, the Electrochemical Surface Area (ECSA) electrode value is known to be 373.601 cm2/mg. Meanwhile, the impedance value is 4.315 Ω and the electrical conductivity value is 6.61x10-4 S/cm. MEA testing using MeOH 3 M fuel produces Open Circuit Voltage (OCV) of 0.650 V. Meanwhile, MEA performance testing uses a mixture of methanol and ethanol 2 M in loading conditions obtained the best mixture of fuel composition is methanol: ethanol = 90:10 with a maximum power density of 4.34 mW/cm2 and is able to maintain the voltage at 0.649 V under conditions of 6.875 mA/cm2. The results also showed that the volume of ethanol which was too high resulted in a decrease in cell performance in the fuel mixture caused by the competition of adsorption between competing methanol and ethanol occupying the active site of the catalyst.Keywords: DAFC, fuel cell, Pt-Ru/C, ethanol, methanol, Open Circuit Voltage